PELATIHAN TEKNIS SUPERVISI KLINIS BAGI PENGAWAS DAN KEPALA SEKOLAH DI KECAMATAN DIMEMBE - Jetty Fientje Kaunang (LPPM UNIMA, 2016)
This training aims to increase knowledge and skills in supervision using the clinical supervising technique for supeintendents and head masters. This training is very useful especially for the duty as supervisors for teachers that are in need of guidance. Stages in training clinical supervision training are informing and the training it self. According to the stages that have been done, it is concluded that the conduction of clinical supervision technique is very helpful for superintendents and head masters in their duty to help, guide the teachers in correcting and adding value to studying and teaching process in schools.